Reconstrucción del patrón alimenticio de dos poblaciones prehistóricas de la Meseta Norte - López-bueis, Inmaculada; Trancho, Gonzalo J.; Fabián, Francisco Javier; Robledo, Beatriz (Complutum, 1996)
Sin resumen